(untitled) (Research, Society and Development, 2020)
Resistance exercise (weight training) is prescribed with scientific bases suggested by the literature with the objective of hypertrophy and endurance, which will depend on the systematization of the training. Among these scientific bases, there is the interval between the training series, from one to three minutes of rest. The aim of this study was to analyze different recovery intervals between sets in squat training on the Smith machine for muscle hypertrophy with intervals of 60, 120 and 180 seconds between sets. Twenty male volunteers, who had been practicing weight training for more than 1 year uninterrupted, were evaluated. Five sets were performed for each training session in the stipulated exercise and the interval evaluated between sets, with a rest of 96 hours of rest for the performance of another training session. The test of a maximum repetition (1RM) was performed to determine the intensity of 80% of 1RM to perform the squat training on the Smith machine with five series of 12 repetitions with an interval between the series of 60, 120 and 180 seconds of interval. It is concluded in this study that none of the intervals evaluated for muscle hypertrophy were sufficient for those evaluated to perform the number of 12 repetitions with an intensity of 80% of 1RM, with a decrease in the number of repetitions during the series performed in training.